Bring Your Own Device Adoption Readiness in a South African University. Issue 3 (2nd October 2018) - Ruxwana, Nkqubela; Msibi, Mncedisi; Mahlangu, Thabo
ABSTRACT: With the rapid evolution of information and communication technologies, particularly the radical growth in mobile computing, mobile learning (m-learning) offers incredible opportunities, especially in the area of higher education. Subsequently, a number of students have started to adapt the way of using portable mobile devices, such as smartphones, in higher education institutions. This trend, where students from higher education institutions are allowed to bring their own personal mobile devices, such as smartphones, for learning purposes using the institution's network to access data and other academic material in order to complete their academic tasks, is referred to as bring your own device (BYOD). Most higher education institutions in developed countries have adopted and implemented this strategy in order to support students' engagement and potentially enhance students' learning experience. However, the rate of BYOD adoption in developing countries is slow, even though the majority of tertiary students and staff already own one or more smart mobile devices and are familiar with using them for both personal and educational purposes. Barriers to BYOD adoption include lack of readiness on the side of institutions in terms of comprehensive policies that govern the use of these devices, lack of inclusive infrastructure readiness, and limited top management support—all of which are essential for the successful adoption of the BYOD strategy. The purpose of this article is to assess the readiness status of South African universities to adopt BYOD for education purposes, using a conceptualised BYOD readiness assessment framework.